2018
DOI: 10.1590/s1982-21702018000300019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pinus Elliottii Growth With Multitemporal Landsat Data: A Study Case in Southern Brazil

Abstract: Remote sensing data are a key proxy to forest monitoring and management at local, regional and global scales. Considering the hypothesis that NDVI and EVI can be used at least during one decade to monitor Pinus elliottii in Southern Brazil, the objective of this study was to identify saturation time after planting of these vegetation indices in a Pinus elliottii plantation and the most suitable index by adjusting theoretical functions to each one of them. Based on Landsat Surface Reflectance Higher-Level Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
2
Order By: Relevance
“…On the other hand, the factor related to the saturation effect of the NDVI and EVI indices in applications on canopies with high biomass may also influence the attenuation of directional effects. In this sense, Käfer et al (2018), when analyzing the saturation time of vegetation indices throughout the productive cycle in the same management area, concluded that the NDVI presented saturation over the canopy at the age of 18 years, while the EVI saturated its response after the plantations completed 14 years. Thus, considering the age of the cultivars in 2019, around 30 years, they are above the response saturation limit of these indices.…”
Section: The Geographical Space In Analysismentioning
confidence: 99%
“…On the other hand, the factor related to the saturation effect of the NDVI and EVI indices in applications on canopies with high biomass may also influence the attenuation of directional effects. In this sense, Käfer et al (2018), when analyzing the saturation time of vegetation indices throughout the productive cycle in the same management area, concluded that the NDVI presented saturation over the canopy at the age of 18 years, while the EVI saturated its response after the plantations completed 14 years. Thus, considering the age of the cultivars in 2019, around 30 years, they are above the response saturation limit of these indices.…”
Section: The Geographical Space In Analysismentioning
confidence: 99%
“…Em razão da área de estudo apresentar alta rotatividade de ciclos de cultivo, apresentando projetos de plantio com as mais variadas idades, optou-se por considerar como área de estudo apenas os povoamentos florestais com idades entre dezoito e quatro anos, correspondentes aos plantios realizados entre os anos de 2000 e 2014. Esta escolha considerou a realização de analises em talhões com dossel fechado, evitandose a ocorrência de mistura espectral oriunda da resposta do substrato e a saturação dos índices de vegetação (Käfer et al, 2018). Figura 1.…”
Section: Caracterização Da áRea De Estudounclassified
“…Vegetation has been monitored traditionally by remote sensing through vegetation indices (IVs) (Käfer et al 2018). Between the available IVs, the most widely applied is the normalized difference vegetation index (NDVI) (Rouse, 1973), which is a numerical indicator adopted to analyze remote sensing measurements and assess whether the target being observed contains live green vegetation or not (Kumar, Shekhar, 2015).…”
Section: Introductionmentioning
confidence: 99%